Exploring the link between Multimorbidity and direct healthcare costs in Ireland: A cross-sectional study - Sharon Walsh; Paddy Gillespie (Journal of Multimorbidity and Comorbidity)
Background Multimorbidity has emerged as a major challenge facing health services globally, which will place a substantial burden on health systems going forward. This paper seeks to estimate the association between multimorbidity and direct healthcare costs among older people in Ireland from a healthcare system perspective. Methods Cross-sectional analysis of data on 8,447 community-dwelling adults aged 50 and over collected between 2009 and 2011 as part of the Irish Longitudinal Study on Ageing. Multivariable generalised linear model regression, employing a log-link and Poisson family distribution, is used to assess the association between self-reported multimorbidity status and direct healthcare costs. Results For the full sample, 21.20% reported having no chronic conditions, 27.39% had one chronic condition, and 51.40% had multimorbidity. After controlling for a range of socio-demographic and health status variables, we found that relative to those reporting no chronic conditions, one chronic condition was associated with additional average annual costs of €513 (95% CIs: 245, 781), increasing to €1277 (95% CIs: 942, 1612) for those with 6 or more chronic conditions. Relative to those reporting 2 chronic conditions, 4 chronic conditions were associated with additional costs of €411 (95% CIs: 106, 716), 5 chronic conditions with €591 (95% CIs: 214, 969), and 6 or more chronic conditions with additional average costs of €1006 (95% CIs: 641, 1371). Conclusion This study finds positive and significant associations between the number of chronic conditions and direct healthcare costs and further highlights the potential economic benefits from preventing the onset and progression of multimorbidity